Combination of bioactive factors and IEIK13 self‐assembling peptide hydrogel promotes cartilage matrix production by human nasal chondrocytes. Issue 4 (31st January 2019) - Dufour, Alexandre; Buffier, Marie; Vertu‐Ciolino, Delphine; Disant, François; Mallein‐Gerin, Frédéric; Perrier‐Groult, Emeline
Abstract: Nasal reconstruction remains a challenge for every reconstructive surgeon. Alloplastic implants are proposed to repair nasal cartilaginous defects but they are often associated with high rates of extrusion and infection and poor biocompatibility. In this context, a porous polymeric scaffold filled with an autologous cartilage gel would be advantageous. In this study, we evaluated the capacity of IEIK13 self‐assembling peptide (SAP) to serve as support to form such cartilage gel. Human nasal chondrocytes (HNC) were first amplified with FGF‐2 and insulin, and then redifferentiated in IEIK13 with BMP‐2, insulin, and T3 (BIT). Our results demonstrate that IEIK13 fosters HNC growth and survival. HNC phenotype was assessed by RT‐PCR analysis and neo‐synthesized extracellular matrix was characterized by western blotting and immunohistochemistry analysis. BIT‐treated cells embedded in IEIK13 displayed round morphology and expressed cartilage‐specific markers such as type II and type IX collagens and aggrecan. In addition, we did not detect significant production of type I and type X collagens and gene products of dedifferentiated and hypertrophic chondrocytes that are unwanted in hyaline cartilage. The whole of these results indicates that the SAP IEIK13 represents a suitable support for hydrogel‐based tissue engineering of nasal cartilage. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 893–903, 2019.